Phase-change materials-based platforms for biomedicine - Chen, Biao-Qi; Pan, Yu-Jing; Zhang, Da-Gui; Xia, Hong-Ying; Kankala, Ranjith Kumar (Frontiers in Bioengineering and Biotechnology, 2022)
Recently, phase-change materials (PCMs) have gathered enormous attention in diverse fields of medicine, particularly in bioimaging, therapeutic delivery, and tissue engineering. Due to the excellent physicochemical characteristics and morphological characteristics of PCMs, several developments have been demonstrated in the construction of diverse PCMs-based architectures toward providing new burgeoning opportunities in developing innovative technologies and improving the therapeutic benefits of the existing formulations. This review systematically emphasizes various PCMs-based nanoplatforms, such as traditional PCMs (liposomes) and their nanoarchitectured composites, including PCMs as core, shell, and gatekeeper, highlighting the pros and cons of these architectures for delivering bioactives, imaging anatomical features, and engineering tissues. Finally, we summarize the article with an exciting outlook, discussing the current challenges and future prospects for PCM-based platforms as biomaterials.